(untitled) (Journal of Nuclear Technology in Applied Science, 2018)
Wastewater contains high levels of organic material, numerous pathogenic microorganisms, as well as nutrients and toxic compounds. Wastewater samples were collected from influent of different wastewater treatment plant. Klebsiella pneumoniae and Acinetobacter lwoffii were isolated from the samples and these isolates were screened for the re duction of wastewater components which estimated by COD (Chemical Oxygen Demand), BOD (Biological Oxygen Demand), and TSS (Total Suspended Solids) values. Wastes reduction by the isolated bacteria using different pH values, incubation temperatures, inoculum volume, static and dynamic condition with different incubation periods and bioremedia ion the variable concentrations of metals in singles and mixtures states were studied. Our investigate show the optimum conditions at pH 7, 35˚C, dynamic condition, 0.5% standard inoculum volume for K.pneumoniae and 2% for A.lwoffii, 48 hours’ incubation period, and metals concentra tions 5ppm.